Система поливу грунту на платформі мікроконтролера Arduino - Литвин, Юлія Олександрівна; Литвин, Юлия Александровна; Lytvyn, Yulia; Строкань, Оксана Вікторівна; Строкань, Оксана Викторовна; Strokan, Oksana (My University, 2019)
UK: Ключовим моментом у процесі вирощування сільськогосподарських культур є забезпечення правильного вологісного режиму ґрунту. Ефективно вирішити це завдання можна за допомогою застосування автоматизованих систем поливу ґрунту, які побудовані на платформі мікроконтролера Arduino. У статті приведена порівняльна характеристика практичної методології вимірювання вологості ґрунту резистивним датчиком YL69 та ємнісним датчиком. Запропонована система автоматизованого поливу ґрунту на базі мікроконтролеру Arduino, яка дозволяє: оптимізувати витрати води при поливі, виконувати полив у заданий час заданою кількістю води, виконувати полив навіть під час відсутності господарів на території поливу та мінімізувати час на полив. RU: Ключевым моментом в процессе выращивания сельскохозяйственных культур является обеспечение правильного влажностного режима почвы. Эффективно решить эту задачу можно с помощью применения автоматизированных систем полива почвы, которые построены на платформе микроконтроллера Arduino. В статье приведена сравнительная характеристика практической методологии измерения влажности почвы резистивным датчиком YL69 и емкостным датчиком. Предложена система автоматизированного полива почвы на базе микроконтроллера Arduino, которая позволяет оптимизировать расходы воды при поливе, выполнять полив в заданное время заданным количеством воды, выполнять полив даже в отсутствие хозяев на территории полива и минимизировать время, выделяемое на полив почвы. EN: The key point in the crops growing process is to ensure the proper soil moisture regime. To obtain a high irrigation effect, it is necessary to accurately determine the rows and volumes of irrigation, which depend on the type of crops, seasons and climatic conditions of the environment. It is possible to solve the problem effectively by constant monitoring the soil moisture content. To do this, we propose the use of automated soil irrigation systems that are based on the Arduino Uno microcontroller plat-form, which uses the Atmega8 controller in an SMD case as the converter. The Arduino Uno board is an open source prototype-based platform based on flexible, easy-to-use hardware and software. In order to optimally select the moisture sensor, the comparative characteristic of the practical methodology of soil moisture measurement by a resistive sensor YL69 and a capacitive sensor is given in the article. For the experiment, the dry sandy soil was used. The comparative analysis of capacitive and resistive moisture sensors has proven the feasibility of using a capacitive sensor in an automatic watering scheme to measure the specific soil resistance. The article also shows the scheme of connecting sensors to the microcontroller. The system of automated soil irrigation on the platform of the Arduino microcontroller is proposed, which allows: to optimize water consumption, to irrigate at the given time with a given amount of water, to perform watering even in the absence of the owners in the watering area, to minimize the time spent on irrigation of the area in comparison with manual watering and convenient and comfortable watering. To manage the work of the system of automated soil irrigation, the software code of the hardware computer platform Arduino has been developed. The created automated irrigation system can be expanded both systematically (for any agrarian enterprises) and functionally (by increasing the number of sensors).
Система полива почвы на платформе микроконтроллера Arduino
The system for irrigation of soil on the Arduino platform
Keywords: автоматизована система; Arduino; мікроконтролер; ємнісний датчик; вологість ґрунту; полив; питомий електричний опір; автоматизированная система; микроконтроллер; емкостной датчик; влажность почвы; удельное сопротивление; automated system; microcontroller; capacitive sensor; soil moisture; watering; resistivity